Patients visiting gastroenterology clinics avoid giving honest history for COVID-19 related symptoms in the pre-clinic triage - Abeer Altaf; Zaigham Abbas; Bushra Shahid; Muhammad Ali Qadeer; Shoukat Ali Samejo; Siyal, Mehreen (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the discrepancy in terms of history related to coronavirus disease-2019 and symptoms given in the pre-clinic triage and to the doctor attending the patient in a gastroenterology clinic. Method: The observational study was conducted from September 2020 to January 2021 at the Gastroenterology outpatient department of Dr Ziauddin Hospital’s Clifton unit in Karachi, and comprised all patients visiting the facility regardless of age and gender. Data was collected using a questionnaire that was first filled up by the receptionist outside the clinic and was then administered again once the patient entered the clinic. Discrepancy on the answers was then checked and associations were determined with clinical assessment. Data was analysed using SPSS 20. Results: Of the 300 patients, 184(61.3%) were males and 116(38.6%) were females. The overall mean age was 55 ± 16.98 (range: 18-92 years). Discrepancy between pre-clinic and in-clinic self-reported data was significant for fever, cough, fatigue, headache, body ache, diarrhoea, sore throat, loss of sense of smell/taste, shortness of breath, and contact with someone positive for coronavirus disease-2019 was significant (p<0.05). Conclusion: Patients were found to be afraid of getting barred from seeing a consultant, had fear of hospital-based isolation or were in denial regarding the pandemic. Key Words: COVID-19, Triage, Questionnaire, Screening, Symptoms.